Implikasi ASEAN-China Free Trade Area (ACFTA) Terhadap Hukum Investasi di Indonesia - , Rizky Ferdian, SIP, Prof. Dr. Nindyo Pramono, S.H., M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The purpose of the research is to determine the form of a free trade area agreement between ASEAN and China and also the influence form of this agreement toward Indonesian investment law. This research also determine the influence of international agreement as a product of international law toward the development of Indonesian investment law. This research using the combination of empirical research and normative research. Empirical legal research is used to find out the primary data by conducting the interview with competent informant. Normative legal research is used to find out secondary data by study carefully all of the regulation that associated with ACFTA. The research results obtained in this study that is the form of ACFTA is treaty of contract, because its only binding the party that signed that agreement. ACFTA agreement is not directly influence investment regulation in Indonesia, but Indonesian must adopt the content of ACFTA agreement into it national law. The establishment of ACFTA demanding to liberalize investment regime between ASEAN and China. It will affect the development of Indonesia's investment law.